Characteristics of agricultural entrepreneurs affecting their ability to repay debts: A case study of customers of the bank for agriculture and agricultural cooperatives (BAAC) - charoensap, wantanee; Punpugdee, Nuttapon (Journal of KMITL Business school, 2024)
The research aims to examine the characteristics of agricultural entrepreneurs affecting their ability to repay loans to agricultural banks and agricultural cooperatives (BAAC). The study investigates two groups of loan customers Performing Loan (PL) and Non-Performing Loan (NPL) groups, totaling 457 participants engaged in agriculture, including farming, industry, commerce, and services. This quantitative research utilizes a questionnaire as a data collection tool. Statistical analysis encompasses both descriptive and inferential statistics. Descriptive statistics utilized in this study include frequency, percentage, mean, and standard deviation. Inferential statistics are applied to test hypotheses concerning the relationships among independent variables. Binary Logistic Regression Analysis is employed to examine variables measured on a nominal scale. This method categorizes loan customers into two groups: those with a normal account status, indicating their ability to repay debts (n = 246), and those with an overdue account status, indicating their inability to repay debts (n = 211). The research findings indicate that agricultural entrepreneurs’ characteristics, such as 1. risk-taking propensity 2. intention to learn and self-develop, and 3. business ethics, can predict whether bank loan customers have the ability to repay debts or not.